2018
DOI: 10.1136/medethics-2017-104608
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation decisions at the end of life: medical views and the juridification of practice

Abstract: This paper provides unique insights into how doctors respond to the changing medico-legal culture and the subsequent effects on patient care. It demonstrates how the juridification of medical practice can occur. It highlights the potential benefit of a structure to support clinicians, patients and relatives in discussing and navigating decisions around care at the end of life in line with the patient's wishes and preferences. Recommendations for future research are made and legal ramifications are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…CPR is frequently presented and framed as a default protocol, and little information is provided on options such as do‐not‐attempt‐to‐resuscitate (DNAR) or comfort measures 15,21 . Physicians refrain from questioning patients' understanding of the procedure, accept decisions as unilateral 22 and provide few opportunities for the patients to express their fears or concerns concerning end of life or CPR 17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPR is frequently presented and framed as a default protocol, and little information is provided on options such as do‐not‐attempt‐to‐resuscitate (DNAR) or comfort measures 15,21 . Physicians refrain from questioning patients' understanding of the procedure, accept decisions as unilateral 22 and provide few opportunities for the patients to express their fears or concerns concerning end of life or CPR 17 …”
Section: Introductionmentioning
confidence: 99%
“…18 CPR is frequently presented and framed as a default protocol, and little information is provided on options such as do-not-attempt-toresuscitate (DNAR) or comfort measures. 15,21 Physicians refrain from questioning patients' understanding of the procedure, accept decisions as unilateral 22 and provide few opportunities for the patients to express their fears or concerns concerning end of life or CPR. 17 Given the pivotal role that communication plays in making these medical decisions, it is important for researchers to explore the explanations given by physicians during actual CPR discussions and how patients develop an understanding and a preference in situations such as routine admission interviews.…”
Section: Introductionmentioning
confidence: 99%
“…Only 3 of the studies reviewed occurred within the Canadian context. Many articles commented on the lack of generalization for study results outside of the country where the study was being conducted due to the impact of factors such as EOL laws, religion and culture on code status decision-making (Anderson et al, 2015;Hartog et al, 2014;Jox et al, 2010;MacCormick et al, 2018). As context plays such an important role in code status discussions, the current study will add valuable insight into how these decisions are communicated amongst ICU teams in Canada.…”
Section: Descriptive Numerical Summary Of the Literaturementioning
confidence: 93%
“…Although Pavlish et al ’s8 study offers a substantial step toward theorising the deferral and avoidance of difficult conversations, their analysis is limited by a reliance on clinicians’ reflections and rationalisations of past practices. In the last decade, several studies have used ethnographic observation methods to explore clinical decision-making about DNACPR and other treatment escalation conversations 9–13. These studies have shown that observational research can locate clinicians’ decisions about DNACPR and attendant conversations, as well as their implications for patient care, within the everyday flows of clinical practice, thereby adding an analytic dimension that cannot be captured by interview and focus group data alone.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, several studies have used ethnographic observation methods to explore clinical decision-making about DNACPR and other treatment escalation conversations. [9][10][11][12][13] These studies have shown that observational research can locate clinicians' decisions about DNACPR and attendant conversations, as well as their implications for patient care, within the everyday flows of clinical practice, thereby adding an analytic dimension that cannot be captured by interview and focus group data alone. This study's aim is to develop an ethnographic account of how and why clinicians defer and avoid ECTP conversations, and how they rationalise these decisions as they happen.…”
mentioning
confidence: 99%